The Effect of Water/Binder (W/B) Variation and Curing Temperature on the Characteristics of Foamed Concrete Incorporated with Palm Shell Ash - Siti Aisyah Nurjannah; Saloma; Arie Putra Usman; Sutanto Muliawan; Haura Siti Maulida; Khikmatur Rasyidah (New Horizons of Science, Technology and Culture Vol. 1, 2025)
Lightweight concrete is the proper material to be applied as a non-structural element in buildings. One type of lightweight concrete is foamed concrete, which reduces the load on the structures and minimises building damage when severe loads occur. Palm shell ash (PSA) is utilised as a partial cement substitution material to increase the compressive strength of lightweight concrete and reduce industrial waste. The purpose of this study was to analyse the performance of foamed concrete incorporated with PSA (FC-PSA), which is influenced by the water/binder (w/b) ratio and steam curing temperature. The XRD and XRF tests were used to determine the reactivity and chemical composition of PSA. The mortar testing is for obtaining slump flow and setting time data. The density and compressive strength tests of hardened FC-PSA used cylinder samples with a diameter of 10 cm and a height of 20 cm. This study was conducted in the Department of Civil Engineering, Sriwijaya University, from December 2024 to March 2025. The density of FC-PSA is 1510.83 kg/m3-1715.92 kg/m3. The test results show that the PSA content reduces the flow properties and increases the setting time. The optimum mix design is the one that uses a w/b ratio of 0.40 and 10% PSA as a partial cement substitute and produces a concrete compressive strength of 12.87 MPa at the age of 28 days. Thus, FC-PSA has a performance that meets the requirements of lightweight incorporated PSA concrete. The optimum steam curing temperature is 60°C, with a w/b of 0.45 and 10% PSA, resulting in a compressive strength of 11.20 MPa at the age of FC-PSA 28 days. PSA has shown potential in replacing part of cement to produce lightweight concrete, thereby reducing industrial waste and conserving nature.